TINDAK PIDANA PENYIARAN DAN SISTEM PERTANGGUNGJAWABAN - Titik Suharti (Perspektif, 2004)
Broadcasting, both television and radio have widely influenced the community. It has positive and negative effects as well. Therefore, it necessarily needs regulation on criminal act and law responsibility of broadcasting. Decree No. 32 of 2002 on Broadcasting, in fact, does not systematically and inconsistently regulate the criminal act and law obligation of broadcasting. There are still many things to be further adjusted so that the purpose of formulating the Decree No. No. 32 of 2002 on Broadcasting can be accomplished.